Historiographical and Historical Basis of the Study of Public Initiatives in the Field of Youth Physical Education in the XIX – Beginning of the XX Century - Prykhod’ko, Hanna (Pedagogical Discourse, 2013)
Analytical review of the literature and document basis of the problem of public initiatives development in the field of youth physical education in the XIX – the beginning of XX century has been carried out in the article. Stratum of archives documents, photo documents, published materials have been characterized: legislative and official statements, facts of record keeping; internal documentation of education institutions, pedagogical out-of-school organizations; statistical data; books literature; pedagogical and special periodicals etc.